Digital Legal Awareness Education for Santri at Darul Falah Islamic Boarding School in Efforts to Prevent Cyberbullying - Sutrisno Sutrisno (Abdimas Paspama, 2025)
Advancements in information technology have significantly impacted social behavior, including among the santri at Islamic boarding schools. On one hand, digital media serves as an effective tool for preaching, education, and communication. On the other hand, negative phenomena such as cyberbullying have emerged, which can lead to psychological, social, and even legal consequences. This community service initiative aims to provide digital legal awareness education to the santri of Darul Falah Islamic Boarding School, helping them understand the legal principles governing online activities under the Electronic Information and Transactions Law (UU ITE) and equipping them with the skills to protect themselves from cyberbullying. The activities include legal counseling, interactive discussions, case studies, and understanding evaluations. The results of the program indicate a significant improvement in the santri's understanding of digital law concepts, relevant provisions of the UU ITE, and strategies for preventing cyberbullying. This initiative is expected to serve as a model for digital legal education within Islamic boarding schools, fostering an ethical, safe, and law-abiding social media culture aligned with Islamic values